By factoring, x can be any real number as long as
y = x(x + 1)(x + 2)
To solve for x in terms of y, you'll need to solve a cubic equation. It's tricky!
http://mathworld.wolfram.com/CubicFormula.html
x³ + 3x² + 2x - y = 0 is of the form:
x³ + (A2)x² + (A1)x +(A0) = 0, where
(A2) = 3, (A1) = 2, and (A0) = -y.
The cubic will have three solutions, two of which may be imaginary. You can look those up from the mathworld link. The real root is:
x = (-1/3)(A2) + S + T, where
S = ³√[R + √D] and T = ³√[R - √D], where
D = Q³ + R²,
Q = [3(A1) + (A2)²] / 9, and
R = [9(A2)(A1) - 27(A0) - 2(A2)³] / 54. I said it was tricky!
Substituting:
R = [9(A2)(A1) - 27(A0) - 2(A2)³] / 54
R = [9(3)(2) - 27(-y) - 2(3)³] / 54
R = [54 + 27y - 54] / 54
R = 27y / 54
R = y / 2
Q = [3(A1) + (A2)²] / 9
Q = [3(2) + (3)²] / 9
Q = [6 + 9] / 9
Q = 15 / 9
Q = 5 / 3
D = Q³ + R²
D = (5 / 3)³ + (y / 2)²
D = 125 / 27 + y² / 4
D = (27y² + 500) / 108
S = ³√{R + √D}; T = ³√{R - √D}
S = ³√{(y / 2) + √[(27y² + 500) / 108]}
T = ³√{(y / 2) - √[(27y² + 500) / 108]}
x = (-1/3)(A2) + S + T
x = (-1/3)(3) + S + T
x = -1 + ³√{(y / 2) + √[(27y² + 500) / 108]} + ³√{(y / 2) - √[(27y² + 500) / 108]}
There's a lot of rationalizing to do with the denominators in there, but at least it's a solution!
2006-10-21 12:05:34
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
6 - 2 x 1 - 4 = 0
2016-05-22 08:14:56
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
y = x^3 + 3x^2 + 2x
Take common factor x out:
y = x * ( x^2 + 3x + 2)
Now solve the quadratic equation x^2 + 3x + 2 and factorize
Or you can use magic:
The sum of all even coefficients is equal to the sum of the odd coeffients, so one root is -1. The product of the two roots is 2. so second root is -2.
Either way you will get:
y = x * (x+1) * (x+2)
2006-10-21 10:02:52
·
answer #3
·
answered by Dr. J. 6
·
0⤊
1⤋
Um.. is this true?
*SPOILER*
x^3+3x^2+2x-y=0
x(x^2+3x+2)=y
x(x+2)(x+1)=y
therefore x=y, x=y-2, x=y-1.. Sorry, usually I do y equals 0 so x=0, x=-2 and x=-1...
2006-10-21 10:08:33
·
answer #4
·
answered by skintouch 2
·
0⤊
1⤋
Go x( x^2 + 3x + 2)=y
x (x + 2)(x + 1) =y
then im sure you can take it from there
2006-10-21 10:09:35
·
answer #5
·
answered by sl_huwanna 1
·
0⤊
1⤋
1. Re-arrange the equation:
x^3 + 3 x^2 + 2x = y
2. Factor out an x:
x(x^2 + 3x + 2) = y
3. "Reverse FOIL"
x(x + 1)(x + 2) = y
4. x can equal y, y - 1, or y - 2. (Change sides, change signs)
2006-10-21 10:03:21
·
answer #6
·
answered by toothpickgurl 3
·
0⤊
2⤋
Cardano solved this. See Wolfram Mathworld on the net. - Cubic formula.
2006-10-21 10:25:05
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
If you subsitute the quadratic formula for x?
I dont know what your asking
Are you trying to solve this for Y
Well hope this helps you think about your answer better.
2006-10-21 10:09:44
·
answer #8
·
answered by pegasis 5
·
0⤊
0⤋
You need the formula for solving cubic equations.
It is complex and tedious but you can find it, and a worked example, at:
http://www.ping.be/~ping1339/cubic.htm
2006-10-21 10:19:16
·
answer #9
·
answered by Wal C 6
·
0⤊
0⤋
for this need more equations to solve
2006-10-21 10:00:53
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋